Analysis of Serials Indexed in Meteorological and Geoastrophysical Abstracts (MGA) - Laurel L. Kristick (Issues in Science and Technology Librarianship)
This article evaluates Meteorological and Geoastrophysical Abstracts (MGA), a bibliographic index to articles on meteorology, astrophysics, geophysics and related fields. It compares the source title coverage of MGA with eight databases that overlap with the subject areas covered in MGA. Titles unique to MGA are examined as to document type, language, subject area and whether they contain peer-reviewed articles. This article also examines the changes made to MGA in 2002, with the move to Cambridge Scientific Abstracts.